Educated : a memoir - Westover, Tara (Random House, New York, 2018)
"Tara Westover was seventeen the first time she set foot in a classroom. Born to survivalists in the mountains of Idaho, she prepared for the end of the world by stockpiling home-canned peaches and sleeping with her "head-for-the-hills bag." In the summer she stewed herbs for her mother, a midwife and healer, and in the winter she salvaged in her father's junkyard. The family was so isolated from mainstream society that there was no one to ensure the children received an education, and no one to intervene when one of Tara's older brothers became violent. As a way out, Tara began to educate herself, learning enough mathematics and grammar to be admitted to Brigham Young University. Her quest for knowledge would transform her, taking her over oceans and across continents, to Harvard and to Cambridge. Only then would she wonder if she'd traveled too far, if there was still a way home. With the acute insight that distinguishes all great writers, Tara Westover has crafted a universal coming-of-age story that gets to the heart of what an education offers: the perspective to see one's life through new eyes, and the will to change it."--Provided by publisher.
Choose the good -- The midwife -- Cream shoes -- Apache women -- Honest dirt -- Shield and buckler -- The Lord will provide -- Tiny harlots -- Perfect in his generations -- Shield of feathers -- Instinct -- Fish eyes -- Silence and the churches -- My feet no longer touch the earth -- No more a child -- Disloyal man, disobedient heaven -- To keep it holy -- Blood and feathers -- In the beginning -- Recitals of the fathers -- Skullcap -- What we whispered and what we screamed -- "I'm from Idaho" -- A knight, errant -- The work of sulphur -- Waiting for moving water -- If i were a woman -- Pygmalion -- Graduation -- The hand of the almighty -- Tragedy -- A brawling woman in a wide house -- Sorcery of physics -- The substance of things -- West of the sun -- Four long arms, whirling -- Gambling for redemption -- The family, morality, and social science -- The princess -- Educated.
HB
Keywords: Westover, Tara -- Family; Women -- Idaho -- Biography; Survivalism -- Idaho -- Biography; Home schooling -- Idaho -- Anecdotes; Women college students -- United States -- Biography; Victims of family violence -- Idaho -- Biography; Subculture -- Idaho; Christian biography; Idaho -- Rural conditions -- Anecdotes; Idaho -- Biography